Multiband, frequency reconfigurable, and metamaterial antennas design techniques: Present and future research directions. Issue 6 (29th January 2018) - Ali, Tanweer; Pathan, Sameena; Biradar, Rajashekhar C.
Abstract : In recent years, the demand for multifunctional components has increased tremendously. Advancement in integrated technology has provided researchers with ample capability to fit diversified applications operating at different frequencies in one wireless device. Integration of multiband antennas in conjunction with frequency reconfigurability offers an optimal antenna design. In addition, the incorporation of metamaterials yields controllable and promising radiation properties. This paper contributes uniquely to the field of antenna design in two ways. First, it provides the domain and technical aspects associated with multiband, frequency reconfigurable, and metamaterial antennas. Second, it provides a critical review of literature. The paper additionally highlights the deficiencies in the design techniques reported in the literature.